Gravity's Rainbow, domination, and freedom - Herman, Luc (The University of Georgia Press, 2013)
When published in 1973, Gravity's Rainbow expanded our sense of what the novel could be. Pynchon's extensive references to modern science, history, and culture challenged any reader, while his prose bent the rules for narrative art and his satirical practices taunted U.S. obscenity and pornography statutes. His writing thus enacts freedom even as the book's great theme is domination: humanity's diminished ""chances for freedom"" in a global military-industrial system birthed and set on its feet in World War II. Its symbol: the V-2 rocket. . ""Gravity's Rainbow, "" Domination, and Freedom broadl